Pengolahan Briket Dari Limbah Tandan Kosong Kelapa Sawit dan Perekat Kanji Sebagai Energi Alternatif - Istiqamah Istiqamah; Zahratunnisa Rahmadina (Program of Biology Education, Universitas Lambung Mangkurat, 2026)
The decreasing availability of petroleum, coupled with the increasing demand for energy, drives the utilization of more sustainable alternative energy sources. One promising alternative is the briquette made from oil palm empty fruit bunch waste, the quality of which is influenced by the type of binder used. This study is an experiment with both quantitative and qualitative approaches to analyze the effect of binder variations, namely starch flour with high adhesive properties, sago flour which is elastic, and rice waste which easily binds charcoal particles. The quality of the briquettes is assessed based on burn duration, smoke odor, and texture. Data were collected through observation and questionnaires, with both quantitative and qualitative descriptive analysis. The results showed that the best formulation was a ratio of 70 gr of empty oil palm fruit bunch charcoal to 50 gr of starch binder to 110 ml of water, which produced briquettes with optimal burning duration, no odor, and a dense texture.